Identification of preoperative radiological risk factors for reoperation following percutaneous endoscopic lumbar decompression to treat degenerative lumbar spinal stenosis - Wang, Aobo; Wang, Tianyi; Zang, Lei; Fan, Ning; Yuan, Shuo; Si, Fangda; Du, Peng (Frontiers in Surgery, 2023)
Background: This study aimed to identify radiological risk factors associated with reoperation after percutaneous transforaminal endoscopic decompression (PTED) for degenerative lumbar spinal stenosis (DLSS). Methods. The preoperative clinical data of 527 consecutive patients with DLSS who underwent PTED were retrospectively reviewed. Overall, 44 patients who underwent reoperation were matched for age, sex, body mass index, and surgical segment to 132 control patients with excellent or good clinical outcomes. Radiological characteristics were compared between the groups using independent sample t-tests and Pearson's chi-square tests. A predictive model was established based on multivariate logistic regression analysis. Results. The analyses revealed significant differences in the presence of lumbosacral transitional vertebra (LSTV, 43.2% vs. 17.4%, p =0.001), the number of levels with senior-grade disc degeneration (2.57 vs. 1.96, p =0.018) and facet degeneration (1.91 vs. 1.25 p =0.002), and the skeletal muscle index (SMI, 849.7 mm2/m2 vs. 1008.7 mm2/m2, p <0.001) between patients in the reoperation and control groups. The results of the logistic analysis demonstrated that LSTV (odds ratio [OR] =2.734, 95% confidence interval [CI]:1.222 – 6.117, p <0.014), number of levels with senior-grade facet degeneration (OR =1.622, 95% CI:1.137 – 2.315, p =0.008), and SMI (OR =0.997, 95% CI:0.995 – 0.999, p =0.001) were associated with reoperation after PTED. The application of the nomogram based on these three factors showed good discrimination (area under the receiver operating characteristic curve 0.754, 95% CI 0.670-0.837) and good calibration. Conclusion: LSTV, more levels with senior-grade facet degeneration, and severe paraspinal muscle atrophy are independent risk factors for reoperation after PTED. These factors can thus be used to predict reoperation risk and to help tailor treatment plans for patients with DLSS.